2014
DOI: 10.1007/s12028-014-9962-2
|View full text |Cite
|
Sign up to set email alerts
|

Artery of Percheron Infarction as an Unusual Cause of Coma: Three Cases and Literature Review

Abstract: Bilateral paramedian thalamic stroke due to AOP occlusion can be life threatening. The early diagnosis relies on MRI with magnetic resonance angiography. Recovery of consciousness is usually rapid and mortality is low, warranting full-code ICU management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
1
34
0
4
Order By: Relevance
“…We also note that most, if not all, cases from the literature describing "thalamic coma" have radiographic evidence of lesions extending into the hypothalamus and brainstem, have exam findings not consistent with the diagnosis of coma, or have clinical signs like ophthalmoplegia that signify damage to the pons or midbrain. [20][21][22] Our findings are also limited in that we focus on level of arousal in the first 12 hours and do not evaluate hypersomnia or circadian rhythm disruptions that have been reported with diencephalic lesions.…”
Section: Discussionmentioning
confidence: 97%
“…We also note that most, if not all, cases from the literature describing "thalamic coma" have radiographic evidence of lesions extending into the hypothalamus and brainstem, have exam findings not consistent with the diagnosis of coma, or have clinical signs like ophthalmoplegia that signify damage to the pons or midbrain. [20][21][22] Our findings are also limited in that we focus on level of arousal in the first 12 hours and do not evaluate hypersomnia or circadian rhythm disruptions that have been reported with diencephalic lesions.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, we noted that it was only 4 of 9 in patients with bilateral infarcts, and 8 of 12 in patients with unilateral paramedian thalamic infarcts, but selective gaze palsy was not recorded. It was reported that 39.2-60% patients with bithalamic paramedian infarcts had memory impairment [12,13]. Only 1 patient with bilateral paramedian thalamic lesion in our cases complained of memory impairment, while 3 patients with unilateral lesions showed memory impairment.…”
Section: Discussionmentioning
confidence: 41%
“…Zappella et al [12] reported that 49 of 120 patients with bilateral thalamic paramedian infarcts had coma but it resolved rapidly (who persisted 2-8 days coma duration). It was quite congruent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…La oclusión de dicha arteria provoca infarto talámico paramedial bilateral sin o con afectación mesencefálica. 4,5 Comunicamos el caso de una paciente mujer de 49 años con factores de riesgo cardiovascular, que fue llevada al servicio de urgencias por presentar mareos y alteración súbita de la conciencia. Las pruebas complementarias de rutina fueron normales.…”
Section: Estimados Editoresunclassified
“…La angiografía no siempre es necesaria para el diagnóstico y resulta útil cuando los métodos anteriores no son concluyentes, o bien, para fines terapéuticos específicos. 2, [4][5][6]8 Otros diagnósticos diferenciales del infarto de la arteria de Percheron son: encefalopatía de Wernicke, mielinolisis extrapontina, encefalitis viral, enfermedad de Wilson, gliomas, enfermedad de Creutzfeldt-Jakob, aunque las lesiones no siguen un territorio vascular conocido. 6,8 El tratamiento suele ser de soporte, idealmente en una unidad de cuidados intensivos, ya que los pacientes presentan menor morbimortalidad.…”
Section: Estimados Editoresunclassified